Framework for managing vital signals in a telemonitoring environment - Rosa, Mariana Cabral da Silva Silveira (2024)
TeleGraft is a European project that aims to develop an arteriovenous graft for hemodialysis patients. After implantation, it is essential to monitor possible anomalies related to blood flow and infections regularly. To this end, Raman spectroscopy techniques and subcutaneous sensors are being studied. This dissertation aimed to develop a telemonitoring system to monitor signals these sensors receive. As the research into the sensors is still ongoing, we aimed to create a more general approach. Therefore, the main goal was to develop a telemonitoring system capable of receiving, storing and visualizing different types of biosignals, such as blood pressure, oxygen saturation and glucose levels. As a secondary goal, the system is intended to predict anomalies, generate reports of clinical problems and alert health professionals if any value is outside the established threshold. Therefore, a web application has been developed for healthcare professionals to add different types of biosignals to monitor their patients according to their needs. In addition, areas dedicated to medication, clinical reports and health questionnaires about the patient’s mental or physical state have also been developed, enabling patients to engage more closely with their healthcare professionals.